A Chebyshev/Legendre polynomial interpolation approach for fingerprint orientation estimation smoothing and prediction - Tashk, Ashkan; Helfroush, Mohammad Sadegh; Dehghani, Mohammad Javad (Frontiers of information technology & electronic engineering, 2010)
We introduce a novel coarse ridge orientation smoothing algorithm based on orthogonal polynomials, which can be used to estimate the orientation field （OF） for fingerprint areas of no ridge information. This method does not need any base information of singular points （SPs）. The algorithm uses a consecutive application of filtering-and model-based orientation smoothing methods. A Gaussian filter has been employed for the former. The latter conditionally employs one of the orthogonal polynomials such as Legendre and Chebyshev type I or II, based on the results obtained at the filtering-based stage. To evaluate our proposed method, a variety of exclusive fingerprint classification and minutiae-based matching experiments have been conducted on the fingerprint images of FVC2000 DB2, FVC2004 DB3 and DB4 databases. Results showed that our proposed method has achieved higher SP detection, classification, and verification performance as compared to competing methods.